River mouth stability of Sungai Papar, Sabah - Mohamad, Noor Asiah (2010)
Kuala Papar is located at a protruding coastline which is directly exposed to waves coming from South China Sea. Sediment bypass take place at this river mouth due to the interference nature of its protruding coastline. In recent years, sand spits have been identified at Kuala Papar. Rapid migration of this sand spit could close up the river mouth and may interrupt navigation activities. This study is conducted to estimate the rate of sedimentation and to determine stability of the river mouth of Kuala Papar. The river mouth stability was investigated by an analysis of the historical shoreline changes and bathymetric changes maps. The shoreline changes map was derived and showed that the location and orientation of the river mouth experience some changes over 23 years due to the sand spit actively growing. Sediment transport rates in the river and within the littoral zone were also estimated. A sediment budget analysis was carried out and resulted in approximately 97071 m3/year of sediment deposited in front of Kuala Papar.